Simple hydrothermal synthesis of defective CeMoSe2 dendrites as an effective electrocatalyst for the electrochemical sensing of 4-nitrophenol in water samples. (24th October 2019) - Ramki, Settu; Sukanya, Ramaraj; Chen, Shen-Ming; Sakthivel, Mani; Wang, Jun Yu
Abstract : This work reports the fabrication of a highly selective and novel electrocatalyst for electrochemical sensing applications. Abstract : This work reports the fabrication of a highly selective and novel electrocatalyst for electrochemical sensing applications. To this aim, CeMoSe2 dendrites were synthesized via hydrothermal synthesis and characterized by using various analytical techniques such as X-ray diffraction (XRD), Raman spectroscopy, field emission scanning electron microscopy (FE-SEM), energy dispersive X-ray (EDX) spectroscopy, transmission electron microscopy (TEM) and X-ray photoelectric spectroscopy (XPS). Further, the conductivity of the as-prepared CeMoSe2 dendritic structure was studied by electrochemical impedance spectroscopy (EIS). The higher conductivity of the CeMoSe2 dendrites made them essential for the electrochemical detection of 4-nitrophenol (4-NP) using cyclic voltammetry (CV) and linear sweep voltammetry (LSV). Electrochemical studies proved that the CeMoSe2 dendrite modified electrode (GCE) shows a low detection limit of 0.0035 μM and a higher sensitivity of 1.24 μA μM −1 cm −2 . Besides this, the real time application of the proposed sensor was tested in river water, which resulted in recovery values of 103.3 to 108.6%. The obtained recovery values also proved that CeMoSe2 /GCE is more suitable for the detection of 4-NP. Thus this simplistic 4-NP sensor is also advantageous due to its simplicity, reliability, low cost, and high stability, rendering it suitable for practical applications in real sample systems.